JURNAL ANALISIS PENGUKURAN DAN PENGAKUAN AKUNTANSI PERSEDIAAN BERDASARKAN PSAK NO.14 PADA TOKO BUKET ALKHANSA CRAFT - Arin Dwi Wulandari; Andrian M. Fikri; Najwan Malika; Citra N Sari; Fahana U Sari (Universitas Muhammadiyah Surakarta, 2024)
Inventory, or goods available for use in making a company's products, is a valuable asset in a company. The company can continue to operate with inventory. Alkhansa Craft Bouquet Shop is a business that operates in the bouquet sector which produces flower bouquets, snack bouquets, or other bouquets which are then sold for a profit. Alkhansa Craft Bouquet Shop is located on Jl. Rajawali Raya, Nilagraha, Gonilan, Kartasura District, Sukoharjo Regency, Central Java 57169. The purpose of conducting this research is to determine the accounting measurement and recognition of inventory based on PSAK No. 14 at the Alkhansa Craft Bouquet Shop. The method used in this research is a qualitative research method which is a method for describing the condition of a company using actual facts that occur in a company. This research concludes that the measurement and recognition of inventory accounting is based on PSAK No.14 at the Alkhansa Bouquet Shop Craft has not been implemented yet.